Women's Experiences of the Premenstrual Body: Negotiating Body Shame, Self-Objectification, and Menstrual Shame. Issue 2 (2nd April 2020) - Ryan, Samantha; Ussher, Jane M.; Perz, Janette
Abstract: Women's body dissatisfaction and shame has been found to increase in the premenstrual phase of the cycle and to be associated with premenstrual distress. However, the factors involved remain little understood. In the present study, 116 women completed an online survey including standardized measures of premenstrual distress, body shame, menstrual shame, and self-objectification, and open-ended questions about premenstrual embodiment. Eight participants completed a semi-structured interview. Significant positive correlations were found between premenstrual distress, body shame, and menstrual shame. Self-objectification was significantly negatively correlated with body shame. Thematic analysis identified internalization and resistance of unrealistic cultural constructions of feminine beauty, concealment of the body, and reduced engagement in body-management behaviors. The implications of the findings for understanding women's premenstrual distress and embodiment are discussed.